Design and development of a phosphoric acid fuel cell - Pholo, Thapelo (My University, 2013)
Fuel cells are electrochemical devices that convert chemical energy of a fuel cell into electricity at high efficiency without combustion. They are viewed as viable power sources for many applications including automobiles, distributed power generation and portable electronics. This dissertation presents the design and development of a phosphoric acid fuel cell. It deals with the experimental studies on phosphoric acid fuel cells and possible integration in replacing the conventional sources of electrical energy in stand-by power supply systems, particularly for use in the telecommunications industry. The design of a DC-DC converter system is also incorporated into the system. The first objective was to establish performance parameters and past studies on phosphoric acid fuel cells and this research revealed that parameters that affect the system's performance include: reactant gas pressures, mass flow rates as well as the operating temperature. Mathematical models in the literature were studied and verified against the simulation models acquired. The second objective was to design and assemble a single cell in order to analyze the cell's performances as well as the operating parameters in order to obtain a model for predicting and simulating the performance of larger fuel cell stacks. The next objective was to analyse from a set of design equations and construct a small DC-DC converter. The converter was used to boost a small fuel cell voltage and regulate it at a higher voltage level. Finally, the performance characteristics of the developed fuel cell, mathematical and simulation models were evaluated and compared. Simulation results for the models and the converter showing a regulated output voltage are presented. Some recommendations for improved system performance and for further studies are suggested.
Thesis (M. Tech. Engineering: Electrical)--Vaal University of Technology
Keywords: Fuel cells; Power sources; Phosphoric acid fuel cells; Alternative power sources; DC-DC converter; 621.312429; Fuel cells